Decentralization in Karnataka - Yashoda, T. (2006)
Different kinds of democracy fit different situation. Good governance requires the thoughtful examination of the principles on which the authority of democratic government rests, the question of who "The people" should be in the concept of "rule by the people". In today's world administrative thinkers thought of decentralized governance as one of the most politically correct deals to be espoused. In the developing world, it is seen as a magical elixir to bring about development involving the local citizenry. Decentralization helps in identifying the needs and preference of people through their direct participation in plan formulation and implementation. It has been accepted in most of the developing countries for its two significant characteristics, ie, I. Accountability and 2. Transparency. They are considered as the important pillars of the decentralized governance that ensure successful deliverfy of the services at the grass roots level. - Reproduced.
Keywords: Decentralization - India - Kerala; Decentralization